Long‐term outcomes of resection versus transplantation for neuroendocrine liver metastases meeting the Milan criteria. Issue 11 (12th August 2022) - Maspero, Marianna; Rossi, Roberta Elisa; Sposito, Carlo; Coppa, Jorgelina; Citterio, Davide; Mazzaferro, Vincenzo
Abstract: Liver resection (LR) is considered the treatment of choice for resectable neuroendocrine liver metastases (NELM), while liver transplantation (LT) is currently reserved for highly selected unresectable patients. We retrospectively analyzed data from consecutive patients undergoing either curative resection or transplantation for liver‐only NELM meeting Milan criteria at a single center between 1984 and 2019. Patients who fit Milan criteria were 48 in the transplantation group and 56 in the resection group. After a median follow‐up of 158 months for the transplantation group and 126 for the resection group, the 10‐year survival rate was 93% for transplantation and 75% for resection ( p  = .007). The 10‐year disease‐free survival rate was 52% for transplantation and 18% for resection ( p  < .001). Transplantation was associated with improved survival at univariate analysis. The median disease‐free interval between surgery and recurrence was 78 months for transplantation vs. 24 months for resection ( p  < .001). The transplantation group had more multisite recurrences (12/25, 48% vs. 5/42, 12% in the resection group, p  = .001), while most recurrences in the resection group were intra‐hepatic (37/42, 88%, versus 2/25, 8% in the transplantation group). In conclusion, LT was associated with improved survival outcomes in NELM meeting the Milan criteria compared with LR. Abstract : Liver transplantation for neuroendocrine liver metastases within Milan Criteria is associated with improved patient outcomes compared to liver resection.